Auditing audits: the method of Oxfordshire Medical Audit Advisory Group. Issue 6812 (16th November 1991) - Derry, J; Lawrence, M; Griew, K; Anderson, J; Humphreys, J; Pandher, K S
Abstract : OBJECTIVES–To develop a systematic method for both summative and formative audit of practice audits, and to use the method to review Oxfordshire practice audits and to plan improvement. DESIGN–Development of a coding system for the audit cycle subsequently used prospectively to assess audits reported to medical audit advisory group coordinators on practice visits. SETTING–All 85 general practices in Oxfordshire, of which 80 were visited by Oxfordshire Medical Audit Advisory Group coordinators. MAIN OUTCOME MEASURES–Satisfaction of criteria for different levels of audit (full, partial, potential, planning or no audit) according to coding scores for practice audits. RESULTS–46 (58%) practices were classified as doing audit, the remainder doing no audit or only collecting data for family health services authority returns. Of audits being undertaken, 55/102 (54%) included planning care or the setting of targets. CONCLUSIONS–The coding system offers the prospect of formative assessment for practices to help them improve their audits, and summative assessment for the family health services authority to satisfy the needs for professional accountability. Its use in Oxfordshire disclosed considerable deficiencies in the process of practice audit. IMPLICATIONS AND ACTION–Practices in Oxfordshire should improve their audits. The advisory groups target to March 1992 is for 50% of practices to be doing full or partial and 25% potential audit and half of the remainder planning audit. Practices are encouraged to include in their audit implementing change, planning care, and agreeing criteria for further assessment.